Etika Pemasaran Bank Syariah - Nurlina Nurlina; Sirajuddin Sirajuddin (Eqien - Jurnal Ekonomi dan Bisnis, 2023)
Abstract. Ethics is part of humans and also an important part in the marketing of Islamic banking. This paper examines marketing ethics in Islamic banking with a literature study. The aim is to provide a global explanation of the marketing ethics of Islamic banks. This study uses a type of qualitative research method with a reference-based approach that focuses on text reviews and literature reviews. The results of this study indicate that Islamic banking has many marketing ethics. Such as promoting products with soft words, marketing that is done well, professionalism, integrity, transparency, placing customers as partners, and emulating the Prophet Muhammad in all life activities. Keywords: Islamic Ethics, Marketing, Islamic Banks